Optimizing Social Media Content Promotion for MSMEs Guided by Karang Taruna in Jayamukti Village - Akbar, Taufik; Ikhsan, M; Ermis Ismail, Iklima (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2024)
This community engagement initiative focuses on enhancing the promotional strategies of micro, small, and medium enterprises (MSMEs) associated with Karang Taruna in Jayamukti Village, aimed at bolstering their visibility and competitiveness in the digital market. Addressing the limited social media presence and promotional skills of these MSMEs, the program introduces targeted training on social media management, content creation, and audience engagement techniques. Using a structured method that combines workshops, hands-on assistance, and mentorship, participants develop skills in producing visually appealing and relevant content for platforms like Instagram and Facebook. Initial results indicate a significant improvement in participants' understanding and application of social media tools, setting a foundation for increased market reach and economic impact on the local community. Future stages of the program will focus on advanced analytics and sustainable promotion strategies, ensuring long-term benefits and self- sufficiency for the MSMEs involved.